Separating, losing and excluding children : narratives of difference - Billington, Tom, 1952- (Master classes in education series., 2000)
"There is considerable public anxiety regarding the whole area of social exclusion, particularly where children are concerned. This book is about those children who are often socially excluded from schools because they are labelled as having 'difficulties' or 'disabilities'." "Tom Billington looks at the processes of exclusion which rely on restricted and simplistic categories of deficit - 'difficulties' or 'disabilities' - which are often broadly organized as being 'learning', 'social/emotional/behavioural' or 'physical/medical' problems. Using fascinating case studies, the author explores theories of language and experience to show how different narratives are produced which shape decisions about children's lives." "Separating, Losing and Excluding Children challenges our assumptions about children who are labelled as 'different' and questions the truth of expert opinion."--Jacket